2016
DOI: 10.1089/vbz.2015.1816
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Paternity in Urban Norway Rats: Extended Ranging for Mates

Abstract: Norway rats are an abundant synanthropic species in urban settings and serve as reservoirs for many pathogens. Attempts to control their populations have met with little success. Recent genetic studies suggest that local populations are structured and few individuals move significant distances, but there is substantial gene flow. To understand these observations and their implications on control strategies, we genotyped 722 rats from 20 alleys in Baltimore to establish paternity for 180 embryos. Up to 88 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…However, despite the small home‐range size of most rats (Davis et al., ; Himsworth et al., ), ectoparasites can still spread between members of different colonies. This may occur when members leave in search for food resources or refuge (Glass et al., ), or when rats from nearby colonies reinvade areas that have been subject to intensive pest control. Also, as rodent populations increase, territories may begin to overlap, which promotes higher contact frequencies and ectoparasite transmission (Altizer et al., ; Davis et al., ; Kerth & Van Schaik, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the small home‐range size of most rats (Davis et al., ; Himsworth et al., ), ectoparasites can still spread between members of different colonies. This may occur when members leave in search for food resources or refuge (Glass et al., ), or when rats from nearby colonies reinvade areas that have been subject to intensive pest control. Also, as rodent populations increase, territories may begin to overlap, which promotes higher contact frequencies and ectoparasite transmission (Altizer et al., ; Davis et al., ; Kerth & Van Schaik, ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, geographical distance may influence the similarity of parasite communities among rat colonies or populations. Very little is known about the movement and dispersal of brown rats in urban landscapes, but recent studies using tracking methods and genetic data indicate that brown rat movements are modest (mean of 100‐200 metres), with some instances of long‐distance dispersal greater than 500 metres (Gardner‐Santana et al., ; Glass, Klein, Norris, & Gardner, ; Heiberg et al., ; Richardson et al., ). This pattern suggests that limited movement and dispersal of brown rats could result in localized parasite communities that become less similar over short geographical distances (Diagne et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that only a small percentage of urban rats move between study sites, with greater movement identified by genetic methods (6.5%, Gardner‐Santana et al., ; 6.8%, Kajdacsi et al., ) than capture–mark–recapture studies for rats caught above ground (0.003% between city blocks, Davis, ) or below ground (0.0% between sewer systems, Heiberg et al., ). Movements by adult males presumably maintain gene flow between nearby colonies (Costa et al., ; Glass, Klein, Norris, & Gardner, ), but results on sex‐biased dispersal have been mixed (Gardner‐Santana et al., ; Heiberg et al., ; Kajdacsi et al., ). However, urban rats are capable of moving several kilometres during relatively rare long‐distance dispersal events (Creel, ), indicating the possibility of gene flow across entire cities.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional approach to reduce SEOV exposure and transmission from wild Norway rats involves rat population control in urban areas. Population reduction is achievable but eradication of rats even from intensely targeted locations is rarely achieved, and populations typically rebound over months even when reductions may exceed 50% (Gardner-Santana et al, 2009;Glass et al, 2016). Control efforts have typically relied heavily on the application of rodenticide, and still do in most urban settings, but the implementation of integrative pest management (IPM) has achieved longer dampening of populations as they can alter the carrying capacity of targeted locations (Keiner, 2005).…”
Section: Controlling Seov Transmissionmentioning
confidence: 99%
“…Examination of maternity/paternity dyads in wild rats showed, however, distinct mate-seeking behavior compared to normal movements. While most non-sexual activities among individual rats occur within 100 m (Glass et al, 1989(Glass et al, , 2016, mates often came from more distant alleys (likely beyond the geographic range of the IPM studies), essentially expanding the potential pool of mates and buffering local populations from perturbations.…”
Section: Controlling Seov Transmissionmentioning
confidence: 99%